Trend Analysis of Physics Prospective Teachers’ Research: An Effort to Improve The Academic Quality of Physics Study Program - Chusni, Muhammad Minan; Zakwandi, Rizki (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
Research should be focused on topics that are appropriate to the needs of the times so that the results of the research can be applied. Students in completing their studies are required to make final assignments in the form of research. Therefore, this study aims to identify the tendency of research of the Physics Education students Indicator the last five years and to determine the theme of educational research studies that allows for further study by Physics Education students in the future. This research was conducted in physics education program with research objects were taken from the written thesis of 2013 until 2017. This research design is a case study with data analysis technique of descriptive qualitative and quantitative. this study found the theme of research studies most studied by Physics Education students were a model of learning and research studies that may still be studied further, namely the evaluation of learning, learning media, and learning strategies on subjects other than temperature and heat and static fluids. The results of this study can be used as a consideration to determine the topic of the thesis and reduce the risk of plagiarism and increase the variety of research in the environment of the study program